GLOBALIZATION AND TRANSNATIONAL ISLAMIC EDUCATION: THE ROLE OF TURKISH MUSLIM DIASPORA IN INDONESIAN ISLAM - Firdaus Wajdi (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2018)
Globalization and the communications revolution have allowed vastly increased flows of ideas and people across the Islamic world, generating new social forms including transnational Islamic movements. Indonesia, as the country with the largest Muslim majority, has attracted Islamic activists from other parts of the world. What is little known is that some of the most active transnational Islamic movements in Indonesia in recent years originate from Turkey. This paper introduces an ethnographic study of one of the lesser known of the major Turkish transnational piety renewal movements that have recently reached Indonesia: the Süleymancıs, the Nurchu, and the Gulen. This case study shows how the Turkish Muslim Diaspora has played significant role in developing a quite unique Islamic education institution with transnational support. The movements have shown a new niche in the saturated Indonesian Islam with a distinct opportunity space.